(3OQI GdZhGU aj ChgGe GdNhGUs - (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj , J (B516 (3g` s ((3GHQGgje GddbGfi s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdPi Ye YHGOg HhXGFa GdYhGQa aEfi QCjJ cKjQkG eef jShG GSeg GdQJH hJSehG HSeI GdGOH aCdaJ gPG GdcJGH JHUQI def JHUQ hJPcQI def CQGO Gf jPcQ hSejJg OQI GdZhGU ai ChgGe GdNhGU s
(3BNQgG (B:s
(3hef Xf eef jdGbi GdMQhH HCf dGjUGH abO Xf YLRkG hef Gddg GSFdge GdJhajb ddebGd GdeJYdb HGdEUGHI hGdaYGd MSf GdGKGHI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs